Bilateral Complete-type Medial Discoid Meniscus - Gökçer UZER; Fatih YILDIZ; Mehmet Anıl PULATKAN; Nuh Mehmet ELMADAĞ (Bezmiâlem Science, 2015)

(untitled)
Discoid meniscus is an uncommon congenital anomaly, and it is rarely seen in the medial compartment of the knee. Literature about bilateral medial discoid meniscus pathology is also limited because one of the knees is usually asymptomatic, although the pathology bilaterally exists. The incidence of bilateral cases should be more than that in current literature because of a number of nondiagnosed cases. In this study, we discuss the approach for a patient with one-sided symptomatic bilateral medial discoid meniscus and present partial meniscectomy as a treatment method.